Sealing tape for rechargeable lithium battery and rechargeable lithium battery including same
A novel sealing tape with an inorganic adhesive and hard coating layer, designed to form a three-dimensional shape upon electrolyte impregnation, addresses the issue of electrode assembly movement in rechargeable lithium batteries, enhancing battery performance by filling gaps and reducing rotation.
Patent Information
- Application Number
- CN202410738126.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-11-23
- Filing Date
- 2024-06-07
- Publication Date
- 2024-12-20
AI Technical Summary
Existing sealing tapes for rechargeable lithium batteries fail to effectively prevent the rotation and movement of the electrode assembly inside the cylindrical battery case due to gaps, leading to performance degradation.
A novel sealing tape with an inorganic adhesive layer and a hard coating layer, designed to have specific thickness variation rates upon electrolyte impregnation, forming a three-dimensional shape that fills the gap between the battery case and the electrode assembly, thereby preventing rotation and movement.
The sealing tape effectively fills the gap between the battery case and the electrode assembly, reducing rotation and movement, and thus preventing performance degradation of the rechargeable lithium battery.
Smart Images

Figure CN119170888A_ABST
Abstract
Description
Technical Field
[0001] One or more embodiments of the present disclosure relate to a sealing tape for a rechargeable lithium battery and a rechargeable lithium battery including the sealing tape. Background Art
[0002] A cylindrical rechargeable lithium battery can be manufactured by the following processes: a process of manufacturing a wound (or similar) electrode assembly by winding a stack of a positive electrode, a separator and a negative electrode (for example, winding into a core shape); a process of storing the wound (or similar) electrode assembly in a cylindrical battery case; and a process of impregnating the wound (or similar) electrode assembly with an electrolyte solution and then sealing it.
[0003] The wound (or similar) electrode assembly can be made smaller than the cylindrical battery case so that it can be accommodated in the cylindrical battery case. As a result, there may be a set or certain gap between the cylindrical battery case and the wound (or similar) electrode assembly.
[0004] However, due to the presence of gaps, the wound (or similar) electrode assembly may easily (and undesirably) rotate or flow (e.g., move) inside the cylindrical battery casing, resulting in performance degradation of the rechargeable lithium battery (e.g., increased internal resistance, damage to electrode tabs, etc.).
[0005] In this regard, a method of attaching a sealing tape having an adhesive layer formed on a PET and / or PP substrate (hereinafter, referred to as a "comparable sealing tape") to the outer peripheral surface of the outermost layer of a wound (or similar) electrode assembly has been proposed. However, in the comparable sealing tape, the PET and / or PP substrate shows a small or insignificant thickness change even if (for example, when) it is impregnated with an electrolyte solution, whereas the adhesive layer changes its thickness if (for example, when) it is impregnated with an electrolyte solution.
[0006] Therefore, comparable sealing tapes are easily detached from a wound type (or similar) electrode assembly impregnated with an electrolyte solution, and have limitations in inhibiting or reducing rotation and / or movement of the wound type (or similar) electrode assembly inside a cylindrical battery case. Summary of the invention
[0007] One or more aspects of the embodiments of the present disclosure relate to a novel sealing tape that can effectively or appropriately prevent or reduce the rotation and / or movement of a wound-type (or similar) electrode assembly inside a cylindrical battery case.
[0008] One or more aspects of an embodiment of the present disclosure are directed to a rechargeable lithium battery including a novel sealing tape for the rechargeable lithium battery.
[0009] Additional aspects will be set forth in part in the description which follows and, in part, will be obvious from the description, or may be learned by practice of the presented embodiments disclosed.
[0010] According to an embodiment of the present disclosure, a sealing tape for a rechargeable lithium battery includes: an inorganic sealing tape, the inorganic sealing tape including an adhesive layer and a hard coating layer located on the adhesive layer, wherein the adhesive layer has adhesiveness and has a thickness variation rate (A) greater than or equal to about 100% and less than or equal to about 120% according to Equation 1, and the hard coating layer does not have adhesiveness and has a thickness variation rate (B) greater than or equal to about 30% and less than or equal to about 70% according to Equation 2:
[0011] Equation 1
[0012] Thickness change rate of adhesive layer (A) = (A2-A1) / A1×100%,
[0013] Where, in equation 1,
[0014] A1 is the thickness of the adhesive layer before impregnation with the electrolyte solution, and
[0015] A2 is the thickness of the adhesive layer after impregnation with the electrolyte solution;
[0016] Equation 2
[0017] Thickness change rate of hard coating (B) = (B2-B1) / B1×100%,
[0018] Where, in equation 2,
[0019] B1 is the thickness of the hard coating layer before being impregnated with the electrolyte solution, and
[0020] B2 is the thickness of the hard coating layer after impregnation with the electrolyte solution.
[0021] According to one or more embodiments, a rechargeable lithium battery includes: a cylindrical battery case; a wound (or similar) electrode assembly housed in the cylindrical battery case; a sealing tape according to a given embodiment, arranged between the outermost layer of the wound (or similar) electrode assembly and a layer (e.g., a lower layer) below (e.g., immediately below) the outermost layer (of the electrode assembly); and an electrolyte solution, impregnating the wound (or similar) electrode assembly and the sealing tape.
[0022] The sealing tape according to one or more embodiments can effectively or appropriately fill (or substantially fill) the gap between the cylindrical battery case and the wound (or similar) electrode assembly by having a three-dimensional shape achieved by impregnation with an electrolyte solution, thereby effectively or appropriately filling the gap between the cylindrical battery case and the wound (or similar) electrode assembly, preventing or reducing the rotation and / or movement of the wound (or similar) electrode assembly, and preventing or reducing the performance degradation of the rechargeable lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] These and / or other aspects will become apparent and more easily understood through the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0024] Figure 1 is a schematic diagram of a sealing tape according to one or more embodiments before being impregnated with an electrolyte solution;
[0025] Figure 2 is a schematic diagram of a sealing tape according to one or more embodiments after being impregnated with an electrolyte solution; and
[0026] Figure 3 is a schematic diagram illustrating a rechargeable lithium battery according to one or more embodiments. DETAILED DESCRIPTION
[0027] Hereinafter, example embodiments will be described in more detail so that those skilled in the art can easily implement them. However, the present disclosure may be embodied in many different forms and is not to be construed as limited to the example embodiments set forth herein.
[0028] The terms used herein are for describing the embodiments only and are not intended to limit the present disclosure. Unless the context clearly indicates otherwise, a singular expression includes a plural expression.
[0029] As used herein, "combinations thereof" may refer to mixtures, stacks, composites, copolymers, alloys, blends, and / or reaction products of the components.
[0030] Here, it will be understood that terms such as "includes," "comprising," and / or "having" are intended to indicate the presence of embodied features (e.g., aspects), quantities, steps (e.g., actions or tasks), elements, or combinations thereof, but do not exclude the possibility of the presence or addition of one or more other features, quantities, steps, elements, or combinations thereof.
[0031] In the drawings, for the sake of clarity, the thickness of layers, films, panels, regions, etc. is exaggerated, and the same reference numerals always represent the same elements, and their repeated description may not be provided in the specification. It will be understood that if (for example, when) an element such as a layer, film, region, or substrate is referred to as being "on" another element, it can be directly on the other element (for example, without any intervening elements being located between them), or there may be intervening elements. Conversely, if (for example, when) an element is referred to as being "directly on" another element, there are no intervening elements.
[0032] The "layer" here includes not only a shape formed on the entire surface if (for example, when) viewed from a plan view, but also a shape formed on a partial surface.
[0033] “Thickness” can be measured, for example, by taking a picture with an optical microscope or an electron microscope such as a scanning electron microscope.
[0034] It will be understood that, although the terms first, second, etc. may be used herein to describe various elements, these elements should not be limited by these terms. These terms are only used to distinguish one element from another element. Therefore, without departing from the teachings of the present invention, the first element may be referred to as the second element. Similarly, the second element may be referred to as the first element.
[0035] As used herein, the term "use" and variations thereof may be considered synonymous with the term "utilize" and variations thereof, respectively.
[0036] As used herein, expressions such as “at least one of…,” “one of…,” “selected from…,” etc., when preceding (preceding) a list of elements, modify the entire list of elements and do not modify the individual elements in the list. For example, “at least one of a, b, and c,” “at least one of a, b, or c,” and “at least one of a, b, and / or c” may refer to only a, only b, only c, both (e.g., simultaneously) a and b, both (e.g., simultaneously) a and c, both (e.g., simultaneously) b and c, all of a, b, and c, or variations thereof.
[0037] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.
[0038] Furthermore, when describing embodiments of the present disclosure, the use of “may” refers to “one or more embodiments of the present disclosure.”
[0039] For ease of description, spatially relative terms such as "under", "below", "lower", "above", "upper", "bottom", "top", etc. may be used herein to describe the relationship of one element or feature to another element or features as shown in the figure. It will be understood that the spatially relative terms are intended to cover different orientations of the device in use or operation in addition to the orientation depicted in the figure. For example, if the device in the figure is turned over, the elements described as "under" or "beneath" other elements or features will then be oriented to be "above" or "on" the other elements or features. Therefore, the term "under" can cover both above and below orientations. The device can be oriented otherwise (rotated 90 degrees or in other orientations), and the spatially relative descriptors used herein should be interpreted accordingly.
[0040] As used herein, the terms "substantially", "about" and similar terms are used as approximate terms rather than as degree terms, and are intended to explain the inherent deviations of measured values or calculated values that will be recognized by those of ordinary skill in the art. As used herein, "about" or "approximately" includes the stated values, and means within the acceptable deviation range of a specific value determined by those of ordinary skill in the art taking into account the measurement in question and the error associated with the measurement of a specific amount (i.e., the limitations of the measurement system). For example, "about" can mean within one or more standard deviations, or within ±30%, ±20%, ±10%, ±5% of the stated value.
[0041] Any numerical range described here is intended to include all sub-ranges of the same numerical precision contained in the described range. For example, the range of "1.0 to 10.0" is intended to include all sub-ranges between the described minimum value 1.0 and the described maximum value 10.0 (and including the described minimum value 1.0 and the described maximum value 10.0), that is, having a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0, such as 2.4 to 7.6. Any maximum numerical limit described here is intended to include all lower numerical limits contained therein, and any minimum numerical limit described in this specification is intended to include all higher numerical limits contained therein. Therefore, the applicant reserves the right to modify this specification and the claims to explicitly describe any sub-ranges contained in the scope explicitly described here.
[0042] Sealing tape
[0043] One or more embodiments provide a sealing tape for a rechargeable lithium battery, the sealing tape comprising an inorganic sealing tape, the inorganic sealing tape comprising an adhesive layer and a hard coating layer on the adhesive layer, wherein the adhesive layer has adhesiveness and has a thickness variation rate (A) greater than or equal to about 100% and less than or equal to about 120% according to Equation 1; the hard coating layer does not have adhesiveness and has a thickness variation rate (B) greater than or equal to about 30% and less than or equal to about 70% according to Equation 2:
[0044] Equation 1
[0045] Thickness change rate of adhesive layer (A) (%) = (A2-A1) / A1×100,
[0046] Where, in equation 1,
[0047] A1 is the thickness of the adhesive layer before impregnation with the electrolyte solution, and
[0048] A2 is the thickness of the adhesive layer after impregnation with the electrolyte solution;
[0049] Equation 2
[0050] Thickness change rate of hard coating layer (B) (%) = (B2-B1) / B1×100,
[0051] Where, in equation 2,
[0052] B1 is the thickness of the hard coating layer before being impregnated with the electrolyte solution, and
[0053] B2 is the thickness of the hard coating layer after impregnation with the electrolyte solution.
[0054] As used herein, "impregnating" a specific object with an electrolyte solution means that the electrolyte solution permeates into the specific object.
[0055] The electrolyte solution is not particularly limited, but may include a non-aqueous organic solvent and a lithium salt; the non-aqueous organic solvent may be ethylene carbonate (EC) and / or dimethyl carbonate (DMC). The non-aqueous organic solvent may also include propylene carbonate (PC) and / or fluorobenzene (FB); and the lithium salt may include LiPF6.
[0056] Based on 100% by volume of the non-aqueous organic solvent, the content of ethylene carbonate (EC) may be about 10% by volume to about 50% by volume, or about 20% by volume to about 40% by volume; the content of dimethyl carbonate (DMC) may be about 40% by volume to about 70% by volume, or about 50% by volume to about 60% by volume; the content of propylene carbonate (PC) may be about 0.1% by volume to about 15% by volume, or about 1% by volume to about 10% by volume, and the content of fluorobenzene (FB) may be about 1% by volume to about 20% by volume, or about 5% by volume to about 15% by volume.
[0057] In the electrolyte solution, the molar concentration of the lithium salt may be about 0.8M to about 1.5M, about 0.9M to about 1.3M, or about 1.0M to about 1.2M.
[0058] The method of measuring the thickness change rate (A) of the adhesive layer is as follows.
[0059] The adhesive layer was cut into width × length = 10 mm × 10 mm to prepare a sample for measuring the thickness change rate, and the thickness of the adhesive layer before being impregnated with the electrolyte solution was measured (A1). Then, each sample for measuring the thickness change rate was impregnated with the electrolyte solution, left in a sealed state at room temperature for 1 day, and then the resulting thickness (thickness of the adhesive layer after impregnation with the electrolyte solution (A2)) was measured.
[0060] Substituting the thickness of the adhesive layer before impregnation with the electrolyte solution (A1) and the thickness of the adhesive layer after impregnation with the electrolyte solution (A2) into Equation 1, the thickness change rate (A) of the adhesive layer is obtained.
[0061] The method of measuring the thickness change rate (B) of the hard coat layer is as follows.
[0062] The hard coating layer was cut into width × length = 10 mm × 10 mm to prepare a sample for measuring the thickness change rate, and the thickness of the hard coating layer before being impregnated with an electrolyte solution was measured (B1). Then, each sample for measuring the thickness change rate was impregnated with an electrolyte solution, placed in a sealed state at room temperature for 1 day, and then the resulting thickness (thickness of the hard coating layer after being impregnated with an electrolyte solution (B2)) was measured.
[0063] By substituting the thickness of the hard coating layer before being impregnated with the electrolyte solution (B1) and the thickness of the hard coating layer after being impregnated with the electrolyte solution (B2) into Equation 2, the thickness change rate (B) of the hard coating layer is obtained.
[0064] Figure 1Schematic diagram of the novel sealing tape 200 of one or more embodiments before being impregnated with an electrolyte solution. Before the novel sealing tape of the given embodiment is impregnated with an electrolyte solution, two objects separated and / or separated (e.g., separated or spaced apart) from each other can be effectively or properly fixed by the mutual balance between the adhesive force of the adhesive layer 220 and the adhesive force of the hard coating layer 210.
[0065] Figure 2 Schematic diagram of the novel sealing tape 200 of one or more embodiments after being impregnated with an electrolyte solution. After the novel sealing tape of one or more embodiments is impregnated with an electrolyte solution, a three-dimensional shape that can fill (or substantially fill) a gap between two objects spaced apart from each other is achieved by balancing the thickness change that occurs after the adhesive layer 220 and the hard coating layer 210 are impregnated with the electrolyte solution.
[0066] Therefore, the novel sealing tape of one or more embodiments effectively or appropriately fills (or substantially fills) the gap between the cylindrical battery case and the wound (or similar) electrode assembly through the three-dimensional shape achieved (or obtained) by electrolyte impregnation, thereby preventing or reducing the rotation and / or movement of the wound (or similar) electrode assembly inside the cylindrical battery case and the performance degradation of the rechargeable lithium battery.
[0067] The novel sealing tape of one or more embodiments may be attached to the outer peripheral surface of the outermost layer of a wound (or quasi) electrode assembly, but may be placed between the outermost layer of a wound (or quasi) electrode assembly and its underlying layer (e.g., a layer below (e.g., immediately below) the outermost layer of the electrode assembly).
[0068] Hereinafter, the novel sealing tape of one or more embodiments is described in more detail.
[0069] Thickness variation of adhesive layer and thickness variation of hard coat layer
[0070] Before impregnating one or more embodiments of the novel sealing tape with an electrolyte solution, the thickness of the hard coating layer 210 can be about 2 microns (μm) to about 10 μm, about 3 μm to about 10 μm, or about 3 μm to about 5 μm; the thickness of the bonding layer 220 can be about 5 μm to about 30 μm, about 10 μm to about 30 μm, or about 10 μm to about 25 μm; and the thickness ratio of the hard coating layer 210 to the bonding layer 220 can be about 1:3 to about 1:10, about 1:3 to about 1:8, or about 1:3 to about 1:7.
[0071] After impregnating one or more embodiments of the novel sealing tape with an electrolyte solution, the adhesive layer 220 may have a thickness variation rate (A) according to Equation 1 of greater than or equal to about 100% and less than or equal to about 120% or greater than or equal to about 110% and less than or equal to about 120%; and the hard coating layer 210 may have a thickness variation rate (B) according to Equation 2 of greater than or equal to about 30% and less than or equal to about 70% or greater than or equal to about 40% and less than or equal to about 70%.
[0072] In one or more embodiments, after the novel sealing tape of one or more embodiments is impregnated with an electrolyte solution, the ratio of the thickness change rate (A) of the adhesive layer to the thickness change rate (B) of the hard coating layer may be about 1.5:1 to about 3:1 or about 1.7:1 to about 3:1.
[0073] If the above range is satisfied, a three-dimensional shape that can appropriately fill (or substantially fill) a gap between two objects spaced apart from each other may be achieved by balancing thickness changes occurring after each of the adhesive layer 220 and the hard coating layer 210 is impregnated with an electrolyte solution.
[0074] However, if the thickness variation rate (A) of the adhesive layer 220 according to Equation 1 is less than the above range, it may not be sufficient to fix (e.g., adhere) two objects spaced apart from each other. If the thickness variation rate (A) of the adhesive layer 220 according to Equation 1 exceeds the above range, the volume of the cylindrical battery case may be excessively (e.g., undesirably or inappropriately) expanded.
[0075] In one or more embodiments, if the thickness variation rate (B) of the hard coating layer 210 according to Equation 2 does not satisfy the above range, the thickness variation of the hard coating layer 210 may not be properly coordinated with the thickness variation of the adhesive layer 220. The above also applies if the ratio of the thickness variation rate (A) of the adhesive layer to the thickness variation rate (B) of the hard coating layer does not satisfy the above range.
[0076] Gel fraction of adhesive layer
[0077] The adhesive layer may have a gel fraction of greater than or equal to about 70wt%, greater than or equal to about 75wt%, or greater than or equal to about 80wt%. If the gel fraction of the adhesive layer is less than about 70wt%, the adhesive layer may swell and disperse. The upper limit of the gel fraction of the adhesive layer is not particularly limited, but may be less than about 100wt%.
[0078] The gel fraction of the adhesive layer can be obtained by the following method.
[0079] Take 1g (W0) of the sample for gel fraction measurement and put it in a 20mL vial, add 1,2,4-trichlorobenzene (about 10mL) to fully or appropriately immerse the sample for gel fraction measurement, and then heat the resultant at 130°C for greater than or equal to about 2 hours. The heated solution is filtered and separated using a 200-mesh wire mesh. Here, the unfiltered and undissolved components are washed twice in a xylene solution and then dried in a hot air oven at 120°C for 12 hours. Finally, the dried undissolved component (W) is measured, and the gel fraction is calculated using Equation 3.
[0080] Equation 3
[0081] Gel fraction (%) = (W / W0) × 100.
[0082] In Equation 3, W is the weight of the dried undissolved component; and W0 is the weight of the initial bonding layer sample, ie, 1 g.
[0083] Peel strength of adhesive layer
[0084] The adhesive layer can achieve a set or specific peel strength due to its adhesive properties.
[0085] For example, the adhesive layer may have a T-Peel peel strength of about 40 gf / cm or more, about 50 gf / cm or more, about 60 gf / cm or more, or about 110 gf / cm or more, measured at a peeling speed of 300 mm / min and a peeling angle of 180 degrees relative to the substrate to which the adhesive layer is attached. The upper limit of the peel strength of the adhesive layer is not particularly limited, but may be less than or equal to about 140 gf / cm.
[0086] The peel strength of the adhesive layer can be measured by the following method.
[0087] As the substrate to be attached, two copper substrates with a width × length × thickness = 150mm × 10mm × 10μm are prepared. Between the two copper substrates, an adhesive layer with a size of 100mm × 30mm × 12μm (width × height × thickness) is placed to obtain a sample for measuring peel strength. The sample for measuring peel strength is pressurized for 1000 seconds at a pressure of 3.5 bars and at a temperature of 50°C using an autoclave. At 25°C, one copper substrate of the pressurized sample for measuring peel strength is fixed to a universal physical property analyzer (product name: TA.XT_Plus Texture Analyzer, manufacturer: Stable MicroSystems), another copper substrate is moved (e.g., dragged) at a speed of 60mm / min, and the T-peel peel strength is measured.
[0088] Composition of the adhesive layer
[0089] The adhesive layer may include a first acrylic resin.
[0090] The first acrylic resin may be a copolymer of 2-ethylhexyl acrylate and 4-hydroxybutyl acrylate cross-linked with an isocyanate-based cross-linking agent.
[0091] Composition of hard coating
[0092] The hard coating layer may be a thermosetting resin that does not include (eg, excludes) a thermoplastic resin. If the hard coating layer contains a thermoplastic resin, it may melt if heated (eg, when heated) and may not be properly used as a sealing tape.
[0093] The hard coating layer may include an acrylate-based thermosetting resin, an acrylate-based UV-curable resin, a urethane-based thermosetting resin, a urethane-based UV-curable resin, an epoxy-based thermosetting resin, an epoxy-based UV-curable resin, or a combination thereof.
[0094] For example, the hard coating layer may include a second acrylic resin. The second acrylic resin may be a thermosetting resin and may be a copolymer of dipentaerythritol hexaacrylate, pentaerythritol tetraacrylate, and ethoxylated trimethylolpropane triacrylate.
[0095] Rechargeable lithium battery
[0096] One or more embodiments provide a rechargeable lithium battery, comprising: a cylindrical battery case; a wound (or similar) electrode assembly housed in the cylindrical battery case; a novel sealing tape of one or more embodiments, arranged between the outermost layer of the wound (or similar) electrode assembly and its lower layer (e.g., a layer below (e.g., immediately below) the outermost layer of the electrode assembly); and an electrolyte solution, impregnating the wound (or similar) electrode assembly and the sealing tape.
[0097] The sealing tape of one or more embodiments can effectively or appropriately fill (or substantially fill) the gap between the cylindrical battery case and the wound (or similar) electrode assembly and / or between the outermost layer and the lower layer of the wound (or similar) electrode assembly by having a three-dimensional shape achieved by impregnation with an electrolyte solution. As a result, the sealing tape of one or more embodiments arranged between the outermost layer and the lower layer of the wound (or similar) electrode assembly can inhibit or reduce the rotation and / or movement of the wound (or similar) electrode assembly inside the cylindrical battery case, and can prevent or reduce the performance degradation of the rechargeable lithium battery.
[0098] As described above, the novel sealing tape of one or more embodiments can be attached to the outer peripheral surface of the outermost layer of the wound (or similar) electrode assembly, but in other cases, it is desirable that the sealing tape be placed between the outermost layer of the wound (or similar) electrode assembly and its lower layer. In the latter (other) case, the capacity of the rechargeable lithium battery can be further improved by increasing the density of the positive electrode and / or the negative electrode.
[0099] Figure 3 is a schematic diagram illustrating a rechargeable lithium battery according to one or more embodiments.
[0100] Hereinafter, a rechargeable lithium battery of one or more embodiments will be described in more detail except for descriptions repeated above.
[0101] Wound (or similar) electrode assembly
[0102] The wound type (or like) electrode assembly may be a stacked body in which a positive electrode, a separator, and a negative electrode are sequentially stacked and wound in such a manner that the negative electrode may be the outermost layer.
[0103] Therefore, the fixing force between the outermost layer (eg, negative electrode) of the wound type (or similar) electrode assembly and the lower layer (eg, separator) thereof may be enhanced.
[0104] The length of the sealing tape may be about 0.8 times to about 1.5 times the circumference of the wound type (or similar) electrode assembly.
[0105] A portion of the sealing tape may be exposed to the outside of the outermost layer of the wound (or similar) electrode assembly. For example, if the length of the sealing tape exceeds about 1 times the circumference of the wound (or similar) electrode assembly, the excess length of the sealing tape may be exposed to the outside of the wound (or similar) electrode assembly, and the rotation and / or movement of the wound (or similar) electrode assembly inside the cylindrical battery case may be effectively or appropriately prevented or reduced.
[0106] Positive electrode active material
[0107] The positive electrode active material may include a lithiated intercalation compound that reversibly intercalates and deintercalates lithium ions. For example, the positive electrode active material may include one or more composite oxides of lithium and a metal selected from cobalt, manganese, nickel, and combinations thereof.
[0108] The composite oxide may be a lithium transition metal composite oxide, and specific examples may include lithium nickel-based oxides, lithium cobalt-based oxides, lithium manganese-based oxides, lithium iron phosphate-based compounds, lithium nickel manganese-based oxides not containing cobalt, or combinations thereof.
[0109] As an example, based on 100 mol% of all metals other than lithium in the lithium transition metal composite oxide, the positive electrode active material can be a high nickel-based positive electrode active material having a nickel content (e.g., amount) greater than or equal to about 80 mol%. Based on 100 mol% of all metals other than lithium in the lithium transition metal composite oxide, the content (e.g., amount) of nickel in the high nickel-based positive electrode active material can be greater than or equal to about 85 mol%, greater than or equal to about 90 mol%, greater than or equal to about 91 mol%, or greater than or equal to about 94 mol% and less than or equal to about 99 mol%. High nickel-based positive electrode active materials can achieve relatively or appropriately high capacity and can be applied to high capacity, high density rechargeable lithium batteries.
[0110] For example, a compound represented by any one of the following chemical formulas may be used: Li a A 1-b X b O 2-c D c (0.90≤a≤,1.8, 0≤b≤0.5, 0≤c≤0.05); Li a Mn 2-b X b O 4-c D c (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05); Li a Ni 1-b-c Co b X c O 2-α D α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5, 0<α<2); Li a Ni 1-b- c Mn b X c O 2-α D α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5, 0<α<2); Li a Ni b Co c L 1 d G e O2 (0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, 0≤e≤0.1); Li a NeG b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a CoG bO2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn 1-b G b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn b O4(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn 1-g G g PO4(0.90≤a≤1.8, 0≤g≤0.5); Li (3-f) Fe2(PO4)3(0≤f≤2); and Li a FePO4(0.90≤a≤1.8).
[0111] In the above chemical formula, A can be Ni, Co, Mn or a combination thereof; X can be Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element or a combination thereof; D can be O, F, S, P or a combination thereof; G can be Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V or a combination thereof; and L 1 It may be Mn, Al or a combination thereof.
[0112] Positive electrode
[0113] A positive electrode for a rechargeable lithium battery may include a current collector and a positive electrode active material layer on the current collector. The positive electrode active material layer includes a positive electrode active material and may further include a binder and / or a conductive material.
[0114] The amount of the positive electrode active material may be about 90 wt % to about 99.5 wt % based on 100 wt % of the positive electrode active material layer.
[0115] In one or more embodiments, the positive electrode active material layer may further include a binder and a conductive material. Here, the amount of the binder and the conductive material may be about 0.5 wt % to about 5 wt %, respectively, based on 100 wt % of the positive electrode active material layer.
[0116] The binder is used to make the positive electrode active material particles adhere well or appropriately to each other, and also to attach the positive electrode active material well or appropriately to the current collector. Examples of the binder may be polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth) acrylated styrene-butadiene rubber, epoxy resin, (meth) acrylic resin, polyester resin, nylon, and combinations thereof, but are not limited thereto.
[0117] The conductive material can be used to impart conductivity (e.g., electrical conductivity) to the electrode, and any suitable material that does not cause chemical changes (e.g., does not cause undesirable chemical changes in a rechargeable lithium battery) and conducts electrons can be used in the battery. Examples of the conductive material may include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube; metal-based materials in the form of metal powder and / or metal fiber, including copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0118] Aluminum (Al) may be used as the current collector, but the present disclosure is not limited thereto.
[0119] Negative electrode active material
[0120] The negative electrode active material may be a material that reversibly intercalates / deintercalates lithium ions, lithium metal, a lithium metal alloy, a material capable of doping and dedoping lithium, and / or a transition metal oxide.
[0121] The lithium metal alloy may include lithium and a metal selected from the group consisting of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.
[0122] The material capable of being doped / dedoped with lithium may be a Si-based negative electrode active material and / or a Sn-based negative electrode active material. The Si-based negative electrode active material may include silicon, a silicon-carbon composite, SiO x(0 < x ≤ 2), Si-Q alloy (where Q is selected from alkali metals, alkaline earth metals, group 13 elements, group 14 elements (excluding Si), group 15 elements, group 16 elements, transition metals, rare earth elements, or combinations thereof, and can be selected from, for example, Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof). The Sn-based negative electrode active material can include Sn, SnO2, Sn alloy, or combinations thereof.
[0123] The silicon-carbon composite can be a composite of silicon and amorphous carbon. The average particle size (D 50 ) of the silicon-carbon composite particles can be, for example, about 0.5 μm to about 20 μm. As used herein, unless otherwise defined, the average particle size (D 50 ) refers to the diameter of the particles with a cumulative volume of 50% by volume in the particle size distribution. The average particle size D 50 can be measured by suitable techniques (e.g., using a particle size analyzer, transmission electron microscope images, and / or scanning electron microscope images). Another method can be performed by the following steps: using a measuring device with dynamic light scattering, analyzing the data to count the number of particles for each particle size, and then calculating to obtain the average particle size D 50 . In this specification, when the particles are spherical, "diameter" represents the particle size, and when the particles are non-spherical, "diameter" represents the major axis length.
[0124] According to one or more embodiments, the silicon-carbon composite can be in the form of silicon particles and amorphous carbon coated on the surface of the silicon particles. For example, the silicon-carbon composite can include secondary particles (cores) in which primary silicon particles are aggregated and an amorphous carbon coating (shells) on the surface of the secondary particles. Amorphous carbon can also be present between the primary silicon particles. For example, the primary silicon particles can be coated with amorphous carbon. The secondary particles can be present in an amorphous carbon matrix.
[0125] The silicon-carbon composite can also include crystalline carbon. For example, the silicon-carbon composite can include a core containing crystalline carbon and silicon particles and an amorphous carbon coating on the surface of the core. The crystalline carbon can be artificial graphite, natural graphite, or combinations thereof. The amorphous carbon can include soft carbon and / or hard carbon, mesophase pitch carbonized products, and / or calcined coke.
[0126] When the silicon-carbon composite includes silicon and amorphous carbon, based on 100 wt% of the silicon-carbon composite, the content (e.g., amount) of silicon can be from about 10 wt% to about 50 wt%, and the content (e.g., amount) of amorphous carbon can be from about 50 wt% to about 90 wt%. In one or more embodiments, if (e.g., when) the composite includes silicon, amorphous carbon, and crystalline carbon, based on 100 wt% of the silicon-carbon composite, the content (e.g., amount) of silicon can be from about 10 wt% to about 50 wt%, the content (e.g., amount) of crystalline carbon can be from about 10 wt% to about 70 wt%, and the content (e.g., amount) of amorphous carbon can be from about 20 wt% to about 40 wt%.
[0127] The thickness of the amorphous carbon coating can be from about 5 nm to about 100 nm. The average particle diameter (D 50 ) of the silicon particles (primary particles) can be from about 10 nm to about 1 μm, or from about 10 nm to about 200 nm. The silicon particles can exist alone as silicon, in the form of a silicon alloy, and / or in an oxidized form. The oxidized form of silicon can be represented by SiO x (0 < x ≤ 2). Here, the atomic content (e.g., amount) ratio of Si:O indicating the degree of oxidation can be from about 99:1 to about 33:67. As used herein, if (e.g., when) no other definition is provided, the average particle diameter (D 50 ) represents the diameter of the particles with a cumulative volume of about 50% by volume in the particle size distribution.
[0128] Si-based negative electrode active materials and / or Sn-based negative electrode active materials can be used in combination with carbon-based negative electrode active materials. When using a mixture of Si-based negative electrode active materials and / or Sn-based negative electrode active materials and carbon-based negative electrode active materials, the mixing ratio by weight can be from about 1:99 to about 90:10.
[0129] Negative electrode
[0130] The negative electrode for a rechargeable lithium battery includes a current collector and a negative electrode active material layer on the current collector. The negative electrode active material layer includes a negative electrode active material and may also contain a binder and / or a conductive material.
[0131] Based on 100wt% of the negative electrode active material layer, the content (e.g., amount) of the negative electrode active material may be about 90wt% to about 99.5wt%, for example, about 95wt% to about 99.5wt%. Based on 100wt% of the negative electrode active material layer, the content (e.g., amount) of the binder may be about 0.5wt% to about 5wt%. Based on 100wt% of the negative electrode active material layer, the content (e.g., amount) of the conductive material may be about 0.5wt% to about 5wt%. For example, the negative electrode active material layer may include about 90wt% to about 99wt% of the negative electrode active material, about 0.5wt% to about 5wt% of the binder, and about 0.5wt% to about 5wt% of the conductive material.
[0132] The binder can be used to well or properly attach the negative electrode active material particles to each other, and also to well or properly attach the negative electrode active material to the current collector. The binder can include a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof.
[0133] The non-aqueous binder may include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.
[0134] The aqueous binder can be selected from styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinyl pyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol and combinations thereof.
[0135] When an aqueous binder is used as a negative electrode binder, the negative electrode binder may further include a cellulose compound capable of imparting viscosity. The cellulose compound includes one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, and alkali metal salts thereof. The alkali metal may be Na, K, and / or Li.
[0136] The dry binder may be a polymer material capable of fiberization, and may be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or a combination thereof.
[0137] The conductive material is included to provide electrode conductivity, and any suitable conductive material can be used as the conductive material unless it causes chemical changes (e.g., unless it causes undesirable chemical changes in the battery). Examples of the conductive material may be: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials in the form of metal powder and / or metal fiber, such as copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0138] The negative electrode current collector may include one (eg, at least one) selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof, but the present disclosure is not limited thereto.
[0139] Electrolyte solution
[0140] The electrolyte solution for a rechargeable lithium battery includes a non-aqueous organic solvent and a lithium salt.
[0141] The nonaqueous organic solvent serves as a medium for transporting ions participating in the electrochemical reaction of the battery.
[0142] The non-aqueous organic solvent may be a carbonate solvent, an ester solvent, an ether solvent, a ketone solvent, an alcohol solvent, an aprotic solvent or a combination thereof.
[0143] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone, valerolactone, caprolactone, etc. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. Ketone solvents may include cyclohexanone. Alcohol solvents may include ethanol, isopropanol, etc., and aprotic solvents may include nitriles such as R-CN (wherein R is a C2-C20 straight chain, branched or cyclic hydrocarbon group, a double bond, an aromatic ring and / or an ether group), amides (such as dimethylformamide), dioxolanes (such as 1,3-dioxolane and / or 1,4-dioxolane), cyclopentane, etc.
[0144] The non-aqueous organic solvent may be used alone or in a mixture of two or more types (species), and if (for example, when) two or more types (species) are used in a mixture, the mixing ratio may be appropriately or suitably adjusted according to the desired or suitable battery performance which may be widely understood by those skilled in the art.
[0145] According to one or more embodiments, if (eg, when) a carbonate-based solvent is used, cyclic carbonate and chain carbonate may be mixed and used, and the cyclic carbonate and chain carbonate may be mixed in a volume ratio of about 1:1 to about 1:9.
[0146] The non-aqueous organic solvent may also include an aromatic hydrocarbon organic solvent. For example, a carbonate-based solvent and an aromatic hydrocarbon organic solvent may be mixed and used in a volume ratio of about 1:1 to about 30:1.
[0147] In order to improve the cycle life of the battery, the electrolyte may further include ethyl vinyl carbonate, vinylene carbonate and / or ethylene carbonate-based compounds.
[0148] Examples of the ethylene carbonate-based compound may include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.
[0149] The lithium salt dissolved in the organic solvent supplies lithium ions in the battery, allows (e.g., promotes) the basic operation of the rechargeable lithium battery, and improves the transport of lithium ions between the positive electrode and the negative electrode. Examples of lithium salts may include those selected from LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide, LiFSI), LiC4F9SO3, LiN(C x F2 x+1 SO2)(C y F 2y+1 SO2) (wherein x and y are integers of 1 to 20), one or more of lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFOB) and lithium bis(oxalato)borate (LiBOB).
[0150] The concentration of the lithium salt may be used in the range of about 0.1 M to about 2.0 M. If the concentration of the lithium salt is within the above range, the electrolyte solution has appropriate or suitable ion conductivity and viscosity, so that excellent or suitable performance may be achieved, and lithium ions may be efficiently moved.
[0151] Diaphragm
[0152] Depending on the type or kind of the rechargeable lithium battery, there may be a separator between the positive electrode and the negative electrode. The separator may include polyethylene, polypropylene, polyvinylidene fluoride, a multilayer film of two or more layers thereof, and / or a mixed multilayer film (such as a polyethylene / polypropylene double-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polypropylene / polyethylene / polypropylene three-layer separator), etc.
[0153] The separator may include a porous substrate and a coating including an organic material, an inorganic material, or a combination thereof on a surface (eg, one surface or (eg, simultaneously) both surfaces (eg, opposite surfaces or sides)) of the porous substrate.
[0154] The porous substrate may be a polymer selected from the group consisting of polyolefins (such as polyethylene and / or polypropylene), polyesters (such as polyethylene terephthalate, polybutylene terephthalate and / or polyethylene naphthalate), polyacetals, polyamides, polyimides, polycarbonates, polyetherketones, polyaryletherketones, polyetherimides, polyamideimides, polybenzimidazoles, polyethersulfones, polyphenylene oxides, cyclic olefin copolymers, polyphenylene sulfides, fiberglass, and polytetrafluoroethylene. and / or a polymer film formed from any one (at least one) of copolymers and / or mixtures of two or more thereof.
[0155] The porous substrate may have a thickness of about 1 μm to about 40 μm, for example, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm.
[0156] The organic material may include a (meth)acryl copolymer, the (meth)acryl copolymer including a first structural unit and a second structural unit, the first structural unit is derived from (meth)acrylamide, and the second structural unit includes at least one selected from a structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acrylamidesulfonic acid or its salt.
[0157] The inorganic material may include inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof, but the present disclosure is not limited thereto. The average particle size (D 50 ) can be from about 1 nm to about 2000 nm, for example, from about 100 nm to about 1000 nm, or from about 100 nm to about 700 nm.
[0158] The organic material and the inorganic material may be mixed in one coating layer, or may be present in the form of a stack of a coating layer containing an organic material and a coating layer containing an inorganic material.
[0159] The coating may have a thickness of about 0.5 μm to about 20 μm, for example, about 1 μm to about 10 μm, or about 1 μm to about 5 μm.
[0160] Rechargeable lithium battery
[0161] Rechargeable lithium batteries may be classified into cylindrical, prismatic, pouch and / or coin-type (or similar) batteries, etc., according to their shapes. Figure 3 is a schematic diagram showing a rechargeable lithium battery according to one or more embodiments. Figure 3 , the rechargeable lithium battery 100 may include an electrode assembly in which a separator 30 is located between a positive electrode 10 and a negative electrode 20, and a case 50 accommodating the electrode assembly. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte solution. Figure 3 As shown in , the rechargeable lithium battery 100 may include a sealing member 60 that seals the case 50 .
[0162] In addition, compared to the case where the tape is attached between the wound (or similar) electrode assembly and the battery case, a rechargeable lithium battery in which the novel sealing tape of one or more embodiments is applied to the outermost layer of a wound (or similar) electrode assembly can have improved battery capacity by increasing the electrode plate density.
[0163] Example 1
[0164] (1) Preparation of hard coating
[0165] 40 parts by weight of IPA (isopropyl alcohol) and 20 parts by weight of MCS (2-methoxyethanol) as solvents, 13 parts by weight of dipentaerythritol hexaacrylate (DPHA), 12 parts by weight of pentaerythritol tetraacrylate (PETA) and 12 parts by weight of ethoxylated trimethylolpropane triacrylate (TMP3EOTA, EO content is 3 mol) as monomers, and 3 parts by weight of 184 Mix and stir to prepare a hard coating solution.
[0166] The hard coating solution was coated on a release film, dried at 80°C for 1 minute, and then irradiated with 300 mJ / cm2 using a metal halide lamp in a nitrogen atmosphere. 2 The film was irradiated with UV to form a 4 μm thick hard coating.
[0167] (2) Preparation of adhesive layer
[0168] 85 parts by weight of ethyl acetate and 15 parts by weight of toluene as a solvent, 95 parts by weight of 2-ethylhexyl acrylate and 5 parts by weight of 4-hydroxybutyl acrylate as monomers, and 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator were mixed, gently stirred after replacing with a nitrogen atmosphere, and polymerized for 8 hours while maintaining the temperature at 55°C to obtain an acrylic prepolymer having a weight average molecular weight (Mw) of 1,300,000 g / mol and Mw / Mn=1.84.
[0169] 0.05 parts by weight of trimethylolpropane adduct of xylene diisocyanate (product name: Takenate TM D-110N, xylene diisocyanate (XDI, manufacturer: Mitsui Chemicals) to prepare an acrylic adhesive composition.
[0170] The acrylic adhesive composition was coated on the release film and dried at 135° C. for 3 minutes to obtain an adhesive layer having a thickness of 12 μm.
[0171] (3) Manufacturing of sealing tape
[0172] The adhesive layer was transferred onto the hard coating layer to prepare a sealing tape.
[0173] (4) Manufacturing of rechargeable lithium battery cells
[0174] LiNi as the positive electrode active material 0.75 Mn 0.23 Al 0.02 O2, polyvinylidene fluoride as a binder, and acetylene black as a conductive material were mixed in a weight ratio of 96:3:1 and dispersed in N-methylpyrrolidone to prepare a positive electrode active material slurry.
[0175] The positive electrode active material slurry was coated on a 15 μm thick Al foil, dried at 100° C., and then pressed to manufacture a positive electrode.
[0176] Artificial graphite was used as a negative electrode active material, and the negative electrode active material, styrene butadiene rubber binder, and carboxymethyl cellulose were mixed at a weight ratio of 98:1:1 and dispersed in distilled water to prepare a negative electrode active material slurry.
[0177] The negative electrode active material slurry was coated on a 10 μm-thick Cu foil, dried at 100° C., and then pressed to prepare a negative electrode.
[0178] A separator (thickness 10 μm) made of polyethylene was placed between the positive electrode and the negative electrode to prepare a stack, and the stack was wound in such a way that the negative electrode became the outermost layer to manufacture a wound type (or type) electrode assembly (circumference: 64 mm). The sealing tape was cut into a length of 70 mm and placed in the gap between the outermost layer (negative electrode) and the lower layer (separator) of the wound type (or type) electrode assembly. Here, a portion (60 mm) of the sealing tape was exposed to the outside of the wound type (or type) electrode assembly.
[0179] The wound type (or similar) electrode assembly having the sealing tape placed thereon is stored in a cylindrical battery case, an electrolyte solution is injected, and the battery case is sealed to obtain a rechargeable lithium battery cell.
[0180] The electrolyte solution is 1.1 M LiPF6 dissolved in a mixed solvent of ethylene carbonate (EC), dimethyl carbonate (DMC), propylene carbonate (PC) and fluorobenzene (FB) (volume ratio of EC:DMC:PC:FB=30:55:5:10).
[0181] Example 2
[0182] A sealing tape and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that the thickness of the hard coating layer was changed to 3 μm.
[0183] Example 3
[0184] A sealing tape and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that the thickness of the hard coating layer was changed to 5 μm.
[0185] Example 4
[0186] A sealing tape and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that the thickness of the adhesive layer was changed to 10 μm.
[0187] Example 5
[0188] A sealing tape and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that the thickness of the adhesive layer was changed to 20 μm.
[0189] Example 6
[0190] A sealing tape and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that the thickness of the adhesive layer was changed to 25 μm.
[0191] Comparative Example 1
[0192] A sealing tape and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that a 4 μm-thick PET substrate was used instead of the hard coating layer.
[0193] Comparative Example 2
[0194] A sealing tape and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that a 10 μm-thick PP substrate was used instead of the hard coating layer.
[0195] Evaluation Example 1: Thickness Change Rate
[0196] (1) Thickness change rate of adhesive layer
[0197] Each of the adhesive layers according to Examples 1 to 6 and Comparative Examples 1 and 2 was cut into a size of width × length = 10 mm × 10 mm to prepare a sample for measuring the thickness change rate (the initial thickness of each sample was taken as the thickness of each adhesive layer before impregnation with the electrolyte solution, A1). The sample for measuring the thickness change rate was impregnated with the electrolyte solution and sealed, and then allowed to stand at room temperature for 1 day to measure the thickness (as the thickness of the adhesive layer after impregnation with the electrolyte solution, A2).
[0198] The thickness of the adhesive layer before being impregnated with the electrolyte solution (A1) and the thickness of the adhesive layer after being impregnated with the electrolyte solution (A2) were substituted into Equation 1 to calculate the thickness change rate (A) of the adhesive layer.
[0199] The composition of the electrolyte solution is the same as that of the electrolyte solution in Example 1.
[0200] Equation 1
[0201] Thickness change rate of the adhesive layer (A) (%) = (A2 - A1) / A1 x 100.
[0202] In equation 1,
[0203] A1 is the thickness of the adhesive layer before impregnation with the electrolyte solution, and
[0204] A2 is the thickness of the adhesive layer after impregnation with the electrolyte solution.
[0205] (2) Thickness change rate of hard coating layer and base layer
[0206] Each of the hard coatings according to Examples 1 to 6 and the base layers according to Comparative Examples 1 and 2 was cut into a size of width × length = 10 mm × 10 mm to prepare samples for measuring the thickness change rate (the initial thickness of each sample was taken as the thickness of the (example) hard coating or (comparative example) base layer before being impregnated with the electrolyte solution, B1). The samples for measuring the thickness change rate were impregnated with the electrolyte solution and sealed, and then allowed to stand at room temperature for 1 day (the resulting thickness of each sample was taken as the thickness of the (example) hard coating or (comparative example) base layer after being impregnated with the electrolyte solution, B2).
[0207] The thickness B1 of the hard coating layer or the PET substrate or the PP substrate before being impregnated with the electrolyte solution and the thickness B2 of the hard coating layer or the PET substrate or the PP substrate after being impregnated with the electrolyte solution are substituted into Equation 2 to calculate the thickness change rate (B) of the hard coating layer or the PET substrate or the PP substrate. The results are shown in Tables 1 and 2.
[0208] Equation 2
[0209] Thickness change rate of hard coating layer or base layer (B) (%) = (B2-B1) / B1×100
[0210] In equation 2,
[0211] B1 is the thickness of the hard coating or base layer before being impregnated with the electrolyte solution, and
[0212] B2 is the thickness of the hard coating or base layer after impregnation with the electrolyte solution.
[0213] (3) A / B ratio
[0214] In one or more examples, the A / B ratios were obtained from (1) and (2) of Evaluation Example 1 and are shown in Tables 1 and 2.
[0215] Evaluation Example 2: Peel Strength of Adhesive Layer
[0216] The adhesive layers of Examples 1 to 6 and Comparative Examples 1 and 2 were prepared to a size of 100 mm × 30 mm × 12 μm (width × length × thickness). In addition, as the substrate to be attached, two copper substrates of width × length × thickness = 150 mm × 10 mm × 10 μm were prepared.
[0217] The adhesive layer was placed between two copper substrates to obtain a sample for measuring peel strength. The sample for measuring peel strength was pressurized for 1000 seconds at a pressure of 3.5 bar and 50° C. using an autoclave. At 25° C., one copper substrate of the pressurized sample for measuring peel strength was fixed to a general property analyzer (product name: TA.XT_Plus texture analyzer, manufacturer: Stable Micro System), and the other copper substrate was dragged at a speed of 60 mm / min to measure the T-type peeling peel strength. The results are shown in Tables 1 and 2.
[0218] Evaluation Example 3: Gel Fraction
[0219] (1) Gel fraction of adhesive layer
[0220] Each of the adhesive layers of Examples 1 to 6 and Comparative Examples 1 and 2 was taken at 1 g (W0) (or at 1 g (W0)) as a sample for measuring the gel fraction, and after the sample was placed in a 20 mL vial, 1,2,4-trichlorobenzene (about 10 mL) was added thereto to fully immerse the sample, and then heated at 130 ° C for 2 hours or more. The heated solution was filtered and separated with a 200 mesh screen. Here, the unfiltered and undissolved components were washed twice with a xylene solution and then dried in a hot air oven at 120 ° C for 12 hours. Finally, the undissolved component (W) after drying was measured to obtain the gel fraction according to Formula 3. The results are shown in Tables 1 and 2.
[0221] Equation 3
[0222] Gel fraction (%) = (W / W0) × 100.
[0223] In Equation 3, W is the weight of the dried undissolved component; and W0 is the weight of the initial bonding layer sample, ie, 1 g.
[0224] (2) Gel fraction of hard coat layer and base layer
[0225] Each of the hard coating layers of Examples 1 to 6 and the base layers of Comparative Examples 1 and 2 was evaluated for gel fraction in substantially the same manner as in (1) of Evaluation Example 3.
[0226] Evaluation Example 4: Ability to realize three-dimensional shape of sealing tape
[0227] Each of the rechargeable lithium battery cells of Examples 1 to 6 and Comparative Examples 1 and 2 was stored at room temperature for 1 day. Subsequently, each of the rechargeable lithium battery cells was disassembled to take out the electrode assembly, and then the sealing tape arranged in the gap between the outermost layer (negative electrode) of the wound electrode assembly and its lower layer (separator) was evaluated according to the following criteria. The results are shown in Tables 1 and 2.
[0228] ○: Observe that Figure 2 The three-dimensional shape shown in
[0229] ×: Separated from the wound (or similar) electrode assembly and without Figure 2 The three-dimensional shape shown in .
[0230] Evaluation Example 5: Gap-filling ability of sealing tape
[0231] The gap filling ability of each of the sealing tapes of Examples 1 to 6 and Comparative Examples 1 and 2 was evaluated by the following two methods, and the results are shown in Tables 1 and 2.
[0232] The gap filling ability of the sealing tape was evaluated by a method for evaluating the flow prevention ability of the electrode assembly, and the flow prevention ability of the electrode assembly was evaluated by a residual vibration evaluation method and a residual impact evaluation method.
[0233] (1) Residual vibration evaluation method: A vibration test was performed according to the UN38.3 standard, wherein if the power of the rechargeable lithium battery cell was not measured after the evaluation, it was judged that one terminal was disconnected.
[0234] (2) Residual impact evaluation method: After inserting a rechargeable lithium battery cell into an octagonal cylinder and rotating them, if the power of the cell is not measured after a set or predetermined period of time, it is judged that the terminal is disconnected due to flow.
[0235] The results from both methods were judged according to the following criteria:
[0236] ○: Power was measured after residual vibration evaluation and residual shock evaluation.
[0237] ×: No power was measured after residual vibration evaluation and residual shock evaluation
[0238] (Table 1)
[0239]
[0240] (Table 2)
[0241]
[0242] In Tables 1 and 2, if the values calculated according to Equation 1 and Equation 2 are decimals, the third decimal place is rounded off.
[0243] Summarize
[0244] Each of the sealing tapes of Comparative Examples 1 and 2 evaluated according to Evaluation Examples 1 to 5 did not show a change in the thickness of the substrate layer (i.e., the PET substrate and the PP substrate) even when impregnated with an electrolyte solution, and did not achieve the above Figure 2 , and thus insufficiently fills (eg, fails to fill) a gap between two objects that are separated from each other.
[0245] In contrast, for each of the sealing tapes of Examples 1 to 6, after the adhesive layer and the hard coating layer were impregnated with the electrolyte solution, respectively, the thickness variation balance was achieved as shown in FIG. Figure 2 The three-dimensional shape shown in , thus filling the gap between two objects that are spaced apart from each other.
[0246] Therefore, the sealing tape of one or more embodiments represented by Examples 1 to 6 has a three-dimensional shape between the outermost layer of the wound (or similar) electrode assembly and its lower layer due to being impregnated with an electrolyte solution to effectively fill the gap between the cylindrical battery case and the wound (or similar) electrode assembly.
[0247] As a result, the sealing tape of one or more embodiments arranged between the outermost layer of a wound (or similar) electrode assembly and its lower layer inhibits or reduces the rotation and / or flow of the wound (or similar) electrode assembly in the cylindrical battery case, thereby preventing or reducing the performance degradation of the rechargeable lithium battery cell.
[0248] While the disclosure has been described in conjunction with what are presently considered to be practical example embodiments, it will be understood that the disclosure is not limited to the disclosed embodiments, but, on the contrary, is intended to cover one or more suitable modifications and equivalent arrangements included within the spirit and scope of the appended claims and their equivalents.
[0249] <Reference Numbers>
[0250] 100: Rechargeable lithium battery
[0251] 10: Positive electrode 20: Negative electrode
[0252] 30: Diaphragm
[0253] 50: housing 60: sealing member
[0254] 200: Sealing tape
[0255] 210: Hard coating layer 220: Adhesive layer.
Claims
1. A sealing tape, the sealing tape include: An inorganic sealing tape, comprising an adhesive layer and a hard coating layer on the adhesive layer, wherein the adhesive layer has adhesiveness and has a thickness variation rate A according to Equation 1 of greater than or equal to 100% and less than or equal to 120%, and The hard coating layer has no adhesiveness and has a thickness variation rate B of greater than or equal to 30% and less than or equal to 70% according to Equation 2: Equation 1 Thickness change rate of adhesive layer A = (A2-A1) / A1×100%, Where, in equation 1, A1 is the thickness of the adhesive layer before being impregnated with an electrolyte solution, and A2 is the thickness of the adhesive layer after impregnation with the electrolyte solution; Equation 2 Thickness change rate of hard coating layer B = (B2-B1) / B1×100%, Where, in equation 2, B1 is the thickness of the hard coating layer before being impregnated with an electrolyte solution, and B2 is the thickness of the hard coating after being impregnated with an electrolyte solution, Wherein, the sealing tape is used for a rechargeable lithium battery.
2. The sealing tape according to claim 1, in, A ratio of a thickness variation rate A of the adhesive layer to a thickness variation rate B of the hard coating layer is 1.5:1 to 3:
1.
3. The sealing tape according to claim 1, in, The adhesive layer has a gel fraction greater than or equal to 70 wt %.
4. The sealing tape according to claim 1, in, The adhesive layer has a T-peel peel strength of greater than or equal to 110 gf / cm, the T-peel peel strength being measured at a peeling speed of 300 mm / min and a peeling angle of 180 degrees with respect to a substrate to which the adhesive layer is attached.
5. The sealing tape according to claim 1, in, The adhesive layer includes a first acrylic resin, and The first acrylic resin is a copolymer of 2-ethylhexyl acrylate and 4-hydroxybutyl acrylate cross-linked with an isocyanate cross-linking agent.
6. The sealing tape according to claim 1, in, The hard coating layer includes a second acrylic resin, and The second acrylic resin is a copolymer of dipentaerythritol hexaacrylate, pentaerythritol tetraacrylate and ethoxylated trimethylolpropane triacrylate.
7. A rechargeable lithium battery, the rechargeable lithium battery include: Cylindrical battery case; A wound electrode assembly is located in the cylindrical battery housing; The sealing tape according to claim 1, located between the outermost layer of the wound electrode assembly and its lower layer; and An electrolyte solution is used to impregnate the wound electrode assembly and the sealing tape.
8. The rechargeable lithium battery according to claim 7, in, The wound electrode assembly is: A stack in which a positive electrode, a separator, and a negative electrode are sequentially stacked and wound in such a manner that the negative electrode becomes the outermost layer.
9. The rechargeable lithium battery according to claim 7, in, The length of the sealing tape is 0.8 to 1.5 times the circumference of the wound electrode assembly.
10. The rechargeable lithium battery according to claim 7, in, A portion of the sealing tape is exposed to the outside of the outermost layer of the wound type electrode assembly.
11. The rechargeable lithium battery according to claim 10, in, The portion is interposed between the wound-type electrode assembly and an innermost portion of the cylindrical battery case.
12. The rechargeable lithium battery according to claim 11, in, The portion is in direct contact with the innermost portion.
13. The rechargeable lithium battery according to claim 7, in, The lower layer is located below the outermost layer of the wound electrode assembly.
14. The rechargeable lithium battery according to claim 8, in, The outermost layer is the negative electrode, and the lower layer is the separator.
